(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The competitive environment created by rapid developments and in the industry and business activities has made companies have one choice: to continuously improve their production system so that they can communicate with developments to ensure success in the field of competition. developments in the course of competition The problem of research is determined by the question (does the use of performance evaluation indicators result in continuous improvement?). The aim of the research is to clarify the concept of continuous improvement in addition to the application of performance evaluation indicators as a tool of continuous improvement in Baghdad Company for soft drinks to achieve continuous improvement. The research concluded a number of results, the most important of which that overall performance indicators are not enough to correct dysfunction. But it is necessary to address the constraints, which often appear as stoppages, to make improvements . Also part of the productivity improvement of wages and employees is not Reflected in unit cost reduction due to increase in the price of material inputs . The researchers recommends the need to prepare, provide publically, and use the indicators of performance analysis, regularly , with emphasis on the following: A - ratios of costs components to the total cost including material inputs, inputs of services, fuel and energy, direct labor wages and total wages. B) Prepare and puplish price index number of output and price index number of inputs to isolate the effect of price changes from technical and operational factors in performance analysis. C - It is useful to integrate Technical methods with Performance evaluation to discover opportunities of performance management